2008
DOI: 10.1002/biot.200700206
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent probes to evaluate the physiological state and activity of microbial biocatalysts: A guide for prokaryotic and eukaryotic investigation

Abstract: Many fluorescent techniques are employed to evaluate the viability and activity of microbial cells used in biotechnology. These techniques are sometimes complex and the interpretation of results opened to misunderstanding. Moreover, new developments are constantly proposed especially concerning a more accurate evaluation of the state of the cells including eukaryotic microorganisms. This paper aims at presenting to biotechnologists unfamiliar with fluorescence the principles of these methods and the related po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 77 publications
2
12
0
Order By: Relevance
“…Shorter chains have been reported to be unable to span the bilayer or form hydrophobic interactions with other lipids and proteins. As a result, the fluidity of the bilayer was increased due to the motion of the free acyl chain ends (16,41). Therefore, the decreased carbon chain length contributed to the increase in cell membrane fluidity, which was in agreement with our results for fluorescence anisotropy detected by the DPH probe.…”
Section: Discussionsupporting
confidence: 91%
“…Shorter chains have been reported to be unable to span the bilayer or form hydrophobic interactions with other lipids and proteins. As a result, the fluidity of the bilayer was increased due to the motion of the free acyl chain ends (16,41). Therefore, the decreased carbon chain length contributed to the increase in cell membrane fluidity, which was in agreement with our results for fluorescence anisotropy detected by the DPH probe.…”
Section: Discussionsupporting
confidence: 91%
“…It has also been reported that longer chains more easily span the width of the bilayer, thereby promoting acyl chain packing and making the membrane environment more gel-like; in contrast, shorter chains are unable to span the bilayer and cannot form hydrophobic interactions with other lipids and proteins. As a result, the fluidity and instability of the bilayer increase due to the motion of the free acyl chain ends [7]. Therefore, the increased fatty acid length contributes to the decrease in cell membrane fluidity, which is in agreement with our results in terms of the pyrene excimerization rate (K a ) and rotational diffusion of DPH.…”
Section: Discussionsupporting
confidence: 90%
“…One possible, indirect indicator of the activity of bacterial cells may be the integrity of cellular membranes (Cao-Hoang et al 2008). It is assumed that bacteria are potentially active if their cellular membrane is intact, and potentially dead if their cellular membrane is damaged (Decamp and Rajendran 1998).…”
Section: Determination Of Bacteria With Intact Functioning Cytoplasmmentioning
confidence: 99%